The analysis of struck-by accidents at construction sites in Malaysia - Simudah, Asdia Fathiya; Abas, Nor Haslinda (2024)
The construction industry is notorious for its high risk of accidents compared to other sectors, with 'struck-by' accidents ranking among the top three reported fatal incidents to the Department of Occupational Safety and Health (DOSH). Thus, investigating the primary causes of these accidents and implementing preventive measures is crucial. This study focuses on gathering data from fatal accidents caused by being struck by objects in the construction sector of Peninsular Malaysia, sourced from the DOSH web database. By analyzing real-case examples, key contributing factors and preventive practices are identified and synthesized into a questionnaire distributed solely to safety personnel. A comparison between the perceptions of security personnel and actual cases sheds light on discrepancies. The questionnaire study reveals that equipment malfunction is a significant contributing factor, emphasizing the importance of securely handling tools and equipment during overhead work as a preventive measure. Real-world examinations confirm this finding, highlighting the importance of avoiding the fall zone of heavy equipment, such as cranes and loaders, particularly when carrying loads. Spearman's rank correlation analysis demonstrates diversity in respondents' views on actual situations. Consequently, this study aims to raise awareness among construction practitioners about the importance of reducing struck-by-object accidents by addressing underlying causes effectively.